The lies we were told : politics, economics, austerity and Brexit - Wren-Lewis, Simon (Bristol University Press, 2018)
"Simon Wren-Lewis is one of Britain's most respected economists. Since 2012, his widely read mainly macro blog has been an influential resource for policymakers, academics and social commentators around the world. The Lies We Were Told presents some of his most important work, telling the story of how the damaging political and economic events of recent years were predictable mistakes. With new material including a preface by Novel prize-winner Paul Krugman, these dispatches from the frontline serve as an essential guide to some of the most important economic and political issues facing us today, and as a warning to avert future disasters on this scale"--Back cover